READER-TEXT CONNECTION: REPORTING THE ENGAGEMENT OF HIGH SCHOOL STUDENTS WITH CULTURALLY RELEVANT TEXTS - Dannah Neriah L. Tan (Association for the Teaching of English as a Foreign Language in Indonesia (TEFLIN), 2021)
Maintaining students’ engagement with reading texts that reflect their background knowledge has positive effect on their comprehension. Culturally relevant materials provide more equitable opportunities to students, in the sense that more of them can reap the benefits of being able to connect to the text (Christ & Sharma, 2018). This article aims to identify the characteristics of texts, particularly those categorized as culturally relevant, which make them appropriate for a specific group of students. Three data gathering methods were used: ratings of texts, reflective journals, and discussion points during Literature Circles. Results indicate that the students participating in the study consider that similar experiences, relatability of the story in terms of feelings and motivation conveyed, actions of the characters, and possibility of experiencing the same event are the main factors that made reading texts culturally relevant to them. These text characteristics can guide classroom teachers, materials developers, and curriculum designers in choosing materials and preparing lessons for specific groups of students, as these underscore the importance of text relatability in building and keeping the students’ reading interest and motivation.